2010
DOI: 10.3846/transport.2010.33
|View full text |Cite
|
Sign up to set email alerts
|

The Calculation and Measurement of the Natural Frequencies of the Bucket Wheel Excavator SCHRS 1320/4x30

Abstract: Abstract. Natural frequencies and shapes are the basic dynamic properties of each structure. On the basis of their knowledge, the sensitivity of the structure to a dynamic load could be estimated. While designing, natural frequencies are based on calculations and numerical simulations. However, computational numerical models do not exactly correspond with real structures and there are many details which have to be simplified. It means that the real natural frequencies of structures may differ from the calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…Directions X and Y are actually expected to present vibration-induced stresses due to the excavation process and also due to the constructive structure of the boom. According to [4], the natural frequencies of a BWE are low, and the authors suggested that frequencies greater than 20 Hz be filtered during the vibration measurement process. Based on these theoretical and practical considerations, the number of modes considered was limited to 15.…”
Section: The Dynamic Regime Of Time Response During Excavationmentioning
confidence: 99%
See 1 more Smart Citation
“…Directions X and Y are actually expected to present vibration-induced stresses due to the excavation process and also due to the constructive structure of the boom. According to [4], the natural frequencies of a BWE are low, and the authors suggested that frequencies greater than 20 Hz be filtered during the vibration measurement process. Based on these theoretical and practical considerations, the number of modes considered was limited to 15.…”
Section: The Dynamic Regime Of Time Response During Excavationmentioning
confidence: 99%
“…In [3], an analysis of the vibrations at the level of a BWE's boom was carried out by measuring the accelerations resulting from the sequence: Starting the bucket wheel, starting the conveyor belt, and stopping both drives. In [4], vibration measurements were made while the bucket wheel was suspended by hoisting ropes without contact with the working face and while the bucket wheel was borne by the working face. In both scenarios, an impulsive load was simulated by shooting a rope on which a weight was suspended onto the wheel.…”
Section: Introductionmentioning
confidence: 99%
“…Although the current engineering codes and national standards used in calculations ignore the dynamic character of BWE external loads, the investigations of BWE dynamics are extremely important [6]. The aforementioned studies include problems of determining excitation induced by resistance-toexcavation [4,7,10], problems of determination and measurement of natural frequencies of BWEs' structures as well as their vibrations during mining process [8,9,[12][13][14][15][21][22][23]. a r c h i v e s o f c i v i l a n d m e c h a n i c a l e n g i n e e r i n g x x x ( 2 0 1 5 ) x x x -x x x a r t i c l e i n f o This paper examines influence of constructive parameters on response of BWE SchRs 1760 superstructure ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BWEs operate in very harsh conditions, being exposed to extreme dynamic and stochastic loads. Improvements have been made in the estimation of working loads (Czmochowski, 2008;Bošnjak et al, 2009b;Gottvald and Kala, 2012), calculation methods (Bošnjak et al, 2006;Gottvald, 2010;Rusiński et al, 2010b;, production technologies and monitoring of vital subsystems (Bartelmus, 2006;Rişteiu et al, 2006;Yin et al, 2007;2008;Bartelmus and Zimorz, 2009). However, failures of structural elements (Bošnjak et al, 2009a;Rusiński et al, 2010a; and mechanisms (Dudek et al, 2011;Savković et al, 2011) are almost inevitable during BWE operation.…”
Section: Introductionmentioning
confidence: 99%